Avaliação do controle postural de pacientes em tratamento de hanseníase - Silva, Adriana Aparecida de Oliveira (2021)
Postural control depends on the integration of sensory inputs of vestibular, visual and somatosensory systems. Peripheral neuropathies interfere with sensory motor information sent to the Central Nervous System (CNS) impairing postural reactions to achieve balance. In leprosy, peripheral nervous system (SNP) involvement and motor sensory disorders can worsen with the evolution of the disease, also altering balance. This dissertation was organized in the form of scientific article, with its own methodology. This is a case-control study where 138 participants of both sexes were evaluated and with a mean age of 46 (12.24) years. All participants were informed about the tests and signed the Free and Informed Consent Form. The sample was divided into 5 groups: control group (n:35 participants without leprosy or other neuropathies) and 4 groups with 103 participants in leprosy treatment divided according to distinct plantar sensory alterations. All were submitted to anthropometric evaluation, simplified neurological evaluation and the Lower Extremity Functional Scale. To evaluate postural control, the force platform (model BIOMEC400- EMGSystem do Brasil®, São José dos Campos, SP) was used. The participant remained in an orthostatic position in the posture’s tasks, open base with open and closed eyes and closed base with open and closed eyes. The variables of CoP oscillation recorded were velocity and displacement in the anteroposterior and lateral mean directions. The results showed a statistically significant difference in the comparison between the groups with leprosy and sensory alteration and anesthesia plantar with the groups hypoesthesia leprosy, leprosy without sensory alteration and control group for the variables of oscillation of the pressure center in the anteroposterior and lateral mean directions, mainly in disturbing situations of postural control such as the reduction of the support base and visual restriction. Thus, through this dissertation, it was possible to understand the oscillation variables of the pressure center in this population and these data may contribute to a better physiotherapeutic approach minimizing possible postural instabilities in people affected by leprosy.